Between continuity and change: A comparison of technology use by pre- and post-migration international students and local students - Collin, Simon; Karsenti, Thierry (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education)

(untitled) (CRIFPE, 2019)
Despite the growing number of studies on migrants’ use of technology, few have focused on the case of international students. Because they come from different countries where they have developed variable uses of technology according to country-specific cultural, political, economic, and other factors, international students may have to adapt the way they use technologies in response to new academic and relational customs and demands at their host university. Based on the idea that their technology use after migration is necessarily influenced by the uses they had developed before migration, this article’s objective is to draw a portrait of technology use by international students before and after migration, and in comparison to local students. A sample of 1,325 international students and 251 local students attending two Canadian universities responded to questionnaires, and the responses were analyzed statistically. The results indicate that, overall, international students increase their use of technologies after migration. Some changes observed are associated with student life in general and university studies in particular—they are thus valid for all students, whether or not they are international, while others appear to be attributable to migration and differentiate international students from their local peers. This study contributes to the advancement of knowledge in that it constitutes a first step toward a more nuanced understanding of the role that technology plays in the university integration of international students.